Development of remote real time temperature monitoring system by using wireless sensor network - Nor Suaida, Abd Wahab (2012)
Monitoring system has employed in various applications, including temperature, pressure, flow rate, capacity, acceleration, and so on. This monitoring is commonly use in all area of the world n traditional method of farming, human labors were required to visit the greenhouse at specific time and need to check the temperature level manually. This conventional method is considered time consuming and needs a lot of work and effort. Therefore this research focuses on developing a system that can remotely monitor and predict changes of temperature level in agricultural greenhouse. The objective of the research is to develop the remote real time temperature monitoring system by using Zigbee network. The proposed system has measurement which capable of detecting the level of temperature. This system also has a mechanism to alert farmers regarding the temperature changes in the greenhouse so that early precaution steps can be taken. In this research, several tests had been conducted in order to prove the viability of the system. Test results indicated that the reliability of the system in propagating information directly to the farmers could be gained excellently in various conditions.